Peers Empowering Peers: Boosting Medical Student Learning - Mazumdar, Arijit (Journal of Neonatal Surgery, 2025)
Background: Peer-assisted learning (PAL) involves students from the same program, often at similar levels, mutually supporting each other's education. This method eases the transition into medical training for novices by engaging near-peers who recently navigated similar challenges, fostering deeper content mastery and richer learning experiences. Aim and Objectives: i. Enhance comprehension of course material, confidence, and effective learning habits.ii. Cultivate skills in organization, planning, and collaborative teamwork.iii. Produce competent medical graduates equipped for practice. Methodology: Conducted in the Department of Physiology at Gauhati Medical College, Guwahati, amongst Phase I MBBS students, the project began with faculty sensitization followed by institutional ethical clearance. Students received project orientation and structured, faculty-validated questionnaires were developed for participants and observers. Informed consent was secured. Peer tutors and listeners were paired from Phase I cohorts. Sessions integrated into Physiology practicals, delivering identical competencies (e.g., PY 10.11: Examination of IIIrd–VIth cranial nerves) to all groups. Pre- and post-intervention assessments used MCQs and OSPE for quantitative metrics, supplemented by qualitative feedback questionnaires. Findings: Out of 200 students, 198 engaged fully. Both peer tutors and listeners showed marked post-test gains, with mean assessment scores reflecting significant academic uplift post-PAL (p<0.05). Most students (85%+) reported satisfaction and eagerness for future sessions. Faculty echoed this, deeming PAL feasible, effective, and worthy of expansion across Physiology and other departments. Conclusions: PAL boosts learning outcomes, academic performance, and communication—key for Indian Medical Graduates (IMGs). Students and faculty endorse it as a valuable teaching-learning method (TLM)